PENGARUH SIKLUS KONVERSI KAS, WOMEN ON BOARD DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN - Abi Kresna Lienardi; Saarce Elsye Hatane; Priskila Adiasih (Business Accounting Review, 2018)
This study aimed to examine the direct impact of Cash Conversion Cycle, Women on board and Firm Size on Firm Value. The sample constituted of 119 manufacture companies listed in Indonesia Stock Exchange during the period of 2011- 2016. The data collected from annual reports, then analyzed by using GRETL software. The result revealed that there was negative influence of cash conversion cycle on firm value. However this study failed to find the influence of Women on board and firm size on firm value.